Occupational exposure to toxigenic fungi from Aspergillus flavus complex - Malta-Vacas, Joana (2012)
Bioaerosols are mainly composed of fungal particles, bacteria and plant spores, being fungi responsible for the release of VOCs and micotoxins into indoor environments. Aspergillus flavus is a common opportunistic pathogen causing human infections and is involved in the production of aflatoxin and other secondary metabolites associated with toxic and allergic reactions. Poultry workers are exposed to high concentrations of fungi and are therefore more prone to develop associated pathologies. To evaluate occupational exposure of the workers to Aspergillus flavus and aflatoxins, six animal production facilities were selected, including 10 buildings, from which indoor air samples and outdoor reference samples were obtained. Twenty-five duplicate samples were collected by two methodologies: impactation onto malt extract agar of 25L air samples using a Millipore Air Tester were used to evaluate quantitative (CFU/m3) and qualitative (species identification, whenever possible) sample composition; 300 L air samples collected with the Coriolis Air Sampler into phosphate–saline buffer were used to isolate DNA, following molecular identification of Aspergillus section flavi using nor-1 specific primers by real-time PCR.